Teaching in schools of specialization: problems and the possible solutions - Guarna, Massimo; Volpi, Nila; Aglianò, Margherita; Tiezzi, Giacomo; Corallo, Giulia; Loglisci, Michele; Grasso, Giovanni (Italian Journal of Anatomy and Embryology, 2014)
Teaching of anatomy in post-graduate schools that request it is particularly difficult for the number of hours available, the need not to repeat arguments already addressed in the degree course in medicine, to stimulate the interest of doctors in training and provide anatomical knowledge which are not detached from the clinical practice. To overcome these difficulties we have used in the teaching of anatomy of the post-graduate schools of the neurological-neurosurgical areas and of laryngology-phoniatry a didactic approach, which illustrate, verified for its effectiveness with an evaluation questionnaire submitted to the doctors in training at the end of the course. The essential points of the teaching are: monographic lectures on topics of anatomy related to the clinical field of specific specialization. Treatment of the subjects starting from neurological syndromes or complex brain functions of clinical relevance the understanding of which involves learning of a set of anatomical structures (eg language and cranial nerve, paralytic syndromes associated of the cranial nerves etc).The educational cycle is completed inviting the doctors to present to colleagues and to the professor the anatomical correlates of a published case report, provided to them at the end of the lesson. The teaching of the anatomy that we have illustrated is different from that which is evident from the texts available of clinical neuroanatomy, which treated anatomy of brain regions or of functional systems and reported medical cases that seek to exercise the clinical reasoning ,which purpose is not relevant to the teaching of anatomy .In conclusion even if our didactic approach is limited to some medical specializations and tested on a small number of doctors in training we suggest it as an alternative way to teach anatomy in postgraduate schools.